Intermediate financial reporting - Empleo, Patricia M.; Robles, Nenita S. (Quezon City, Philippines : EDT Book Shop, 2021)
This book is to provide information that is useful to currents and potential investors and other users in making rational investment, credit and similar decision.
CHAPTER 1. Review of the Accounting process -- 2. The Statement of Financial Position and the notes to Financial statements -- 3. The statement of comprehensive Income and the statement of changes in equity -- 4. The statement of Cash Flows -- 5. Earning Per Share -- 6. Interim Reporting and reporting by Operating segments -- 7. Financial reporting for small Entities and Medium sized entities.
Includes bibliographical references.
Keywords: ACCOUNTING